Case Report: Multiple prolactinomas in a young man with Kallmann syndrome and familial hypocalciuric hypercalcemia - Jensterle, Mojca; Janež, Andrej; Vipotnik Vesnaver, Tina; Debeljak, Maruša; Breznik, Nika; Trebušak Podkrajšek, Katarina; Herman, Rok; Fliers, Eric; Battelino, Tadej; Avbelj Stefanija, Magdalena (Frontiers in Endocrinology, 2023)
Introduction: The occurrence of prolactinomas in sex hormone treated patients with central hypogonadism is extremely rare.Case Presentation: We present a Caucasian male patient who was diagnosed with Kallmann syndrome (KS) at age 15 years. Testosterone treatment was started. At age 26 the patient presented with mild headache. MRI revealed two separate pituitary adenomas along with the absence of the olfactory bulbs. Given the presence of marked hyperprolactinemia (17x upper limit of the reference range) the diagnosis prolactinoma was made and treatment with cabergoline was started which resulted in a complete biochemical response and in marked reduction of both adenomas in size. Hypogonadism persisted and testosterone replacement therapy was continued. Genetic testing of genes associated with pituitary tumors, Kallmann syndrome and idiopathic hypogonadotropic hypogonadism was negative. Mild concomitant hypercalcemia in accordance with familial hypocalciuric hypercalcemia (FHH) prompted mutation analysis of the calcium receptor (CASR) gene which yielded a pathogenic inactivating variant.Discussion/Conclusion: The presence of two separate prolactinomas in a patient with KS has not yet been reported in the literature. The effect of sex hormone treatment of KS patients on the possible development of prolactinoma is unknown at present. The occurance of multiple prolactinomas in our patient suggests increased susceptibility. Although CaSR is expressed in GnRH neurons in mouse brain and CaSR deficient mice have a reduced hypothalamic GnRH neuronal population, the relevance of the CASR gene variant in our patient for the KS phenotype is unclear at present.